Auditory Neuropathy as the Initial Phenotype for Patients With ATP1A3 c.2452 G > A: Genotype–Phenotype Study and CI Management - Wang, Wenjia; Li, Jin; Lan, Lan; Xie, Linyi; Xiong, Fen; Guan, Jing; Wang, Hongyang; Wang, Qiuju (Frontiers in Cell and Developmental Biology, 2021)
Objective: The objective of this study is to analyze the genotype–phenotype correlation of patients with auditory neuropathy (AN), which is a clinical condition featuring normal cochlear responses and abnormal neural responses, and ATP1A3 c.2452 G > A (p.E818K), which has been generally recognized as a genetic cause of cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss (CAPOS) syndrome. Methods: Four patients diagnosed as AN by clinical evaluation and otoacoustic emission and auditory brainstem responses were recruited and analyzed by next-generation sequencing to identify candidate disease-causing variants. Sanger sequencing was performed on the patients and their parents to verify the results, and short tandem repeat-based testing was conducted to confirm the biological relationship between the parents and the patients. Furthermore, cochlear implantation (CI) was performed in one AN patient to reconstruct hearing. Results: Four subjects with AN were identified to share a de novo variant, p.E818K in the ATP1A3 gene. Except for the AN phenotype, patients 1 and 2 exhibited varying degrees of neurological symptoms, implying that they can be diagnosed as CAPOS syndrome. During the 15 years follow-up of patient 1, we observed delayed neurological events and progressive bilateral sensorineural hearing loss in pure tone threshold (pure tone audiometry, PTA). Patient 2 underwent CI on his left ear, and the result was poor. The other two patients (patient 3 and patient 4, who were 8 and 6 years old, respectively) denied any neurological symptoms. Conclusion:ATP1A3 p.E818K has rarely been documented in the Chinese AN population. Our study confirms that p.E818K in the ATP1A3 gene is a multiethnic cause of AN in Chinese individuals. Our study further demonstrates the significance of genetic testing for this specific mutation for identifying the special subtype of AN with somewhat favorable CI outcome and offers a more accurate genetic counseling about the specific de novo mutation.